MALDI-TOF MS based procedure to detect KPC-2 directly from positive blood culture bottles and colonies. - Figueroa Espinosa, Roque Arnulfo (2019)
In this study, we identified specific carbapenemase-producing isolates applying an easy and rapid protocol for the detection of mature KPC-2 β-lactamase by MALDI-TOF MS from colony and positive blood culture bottles. In addition, we evaluated the correlation of the ~11,109 Da signal as a biomarker associated with KPC-2 production. A collection of 126 well-characterized clinical isolates were evaluated (including 60 KPC-2-producing strains). Presence of KPC-2 was assessed by MALDI-TOF MS on protein extracts. Samples were prepared using the double layer sinapinic acid technique. In order to identify mature KPC-2, raw spectra were analyzed focusing on the range between m/z 25,000–30,000 Da. A single distinctive peak, at approximately m/z 28,544 Da was found in all clinical and control KPC-2-producing strains, and consistently absent in the control groups (ESBL producers and susceptible strains). This peak was detected in all species independently of where the gene bla KPC-2 was embedded. Statistical results showed 100% sensitivity, CI95%: [94.0%; 100%] and 100% specificity, CI95%: [94.6%; 100%], indicating a promising test with a high discriminative power. KPC-2 β-lactamase could be directly detected from both colonies and blood culture bottles. On the other hand, the m/z 11,109 Da signal determinant was only associated with 32% of Klebsiella pneumoniae and Escherichia coli KPC positive isolates. This MALDI-TOF MS methodology has the potential to detect directly the widespread and clinically relevant carbapenemase, KPC-2, in Enterobacterales with a straightforward, low cost process, assuming MALDI-TOF MS is already adopted as the main identification tool, with clear clinical implications on antibiotic stewardship for early infection treatment.